The multivariate simultaneous unobserved components model and identification via heteroskedasticity - Mengheng Li; Ivan Mendieta-Mu\~noz (The University of Utah, Department of Economics, 2019)
We propose a multivariate simultaneous unobserved components framework to determine the two-sided interactions between structural trend and cycle innovations. We relax the standard assumption in unobserved components models that trends are only driven by permanent shocks and cycles are only driven by transitory shocks by considering the possible spillover effects between structural innovations. The direction of spillover has a structural interpretation, whose identification is achieved via heteroskedasticity. We provide identifiability conditions and develop an efficient Bayesian MCMC procedure for estimation. Empirical implementations for both Okun's law and the Phillips curve show evidence of significant spillovers between trend and cycle components.
Keywords: C11; C32; E31; E32; E52; 330; Unobserved components; Identification via heteroskedasticity; Trends and cycles; Permanent and transitory shocks; State space models; Spillover structural effects